In poster, Chico Buarque: the movie adaptation of the novel Benjamin by Monique Gardenberg - Arruda, Mariana Mendes (2007)
The movie director Monique Gardenberg’s version of the novel Benjamim, by Chico Buarque, takes to the screens the narrative of the former photographic model in two different times and between two feminine characters: Castana Beatriz, in the 1960’s, and Ariela Masé, in the 1990’s. The analysis is elaborated in the light of the contemporary theory about movies adaptation by Brian McFarlane. According to the distributional and integrating functions of narrative – defended by Roland Barthes in the Theory of the Levels (1973) –, which are the pillar of the analysis proposed by McFarlane, this paper examines the two versions of Benjamim and the processes of transfer and adaptation used in the film.